Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Badan Keuangan dan Aset Daerah Kabupaten Minahasa Selatan) - Mamangkey, Injili Ester; Watung, Sjeddie R (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze the influence of accounting information systems and internal control systems on the quality of local government financial reports. This type of research is quantitative. This research was conducted at the Regional Finance and Asset Agency of South Minahasa Regency. The population in this study was 49 ASN BKAD South Minahasa Regency. Sampling used a purposive sampling method. Data collection used a questionnaire. The data analysis technique used in this study was multiple regression analysis. The results of the study indicate that accounting information systems have a positive and significant relationship with the quality of financial reports. Similarly, the internal control system is proven to have a positive and significant influence on the quality of financial reports. With evidence obtained through SPSS 25.